Differential impacts of global change variables on coastal South Atlantic phytoplankton: Role of seasonal variations. (April 2017) - Cabrerizo, Marco J.; Carrillo, Presentación; Villafañe, Virginia E.; Helbling, E. Walter
Abstract: Global change is associated to the increase in temperature (T), nutrient inputs (Nut) and solar radiation in the water column. To address their joint impact on the net community production [NCP], respiration [CR] and PSII performance (ΦPSII ) of coastal phytoplankton communities from the South Atlantic Ocean over a seasonal succession, we performed a factorial design. For this, we used a 2 × 2 × 2 matrix set-up, with and without UVR, ambient and enriched nutrients, and in situ T and in situ T + 3 °C. The future scenario of global change exerted a dual impact, from an enhancement of NCP and ΦPSII during the pre-bloom to an inhibition of both processes towards the bloom period, when the in situ T and irradiances were lower and the community was dominated by diatoms. The increased inhibition of NCP and ΦPSII during the most productive stage of the annual succession could produce significant alterations of the CO2 -sink capacity of coastal areas in the future. Highlights: Future global-change impacts were evaluated on coastal South Atlantic phytoplankton. Nutrient inputs, temperature and UVR effects were tested using a factorial approach. Pre-bloom will be benefited by global-change compared to bloom communities. Seasonal variations also influence the phytoplankton responses to global-change impacts.